Dobutamine treatment reduces inflammation in the preterm fetal sheep brain exposed to acute hypoxia. (September 2018) - Brew, Nadine; Nakamura, Shinji; Hale, Nadia; Azhan, Aminath; Davies, Grace; Nitsos, Ilias; Miller, Suzanne; Walker, David; Wong, Flora
Abstract Background Impaired cerebral autoregulation in preterm infants makes circulatory management important to avoid cerebral hypoxic–ischemic injury. Dobutamine is frequently used as inotropic treatment in preterm neonates, but its effects on the brain exposed to cerebral hypoxia are unknown. We hypothesized that dobutamine would protect the immature brain from cerebral hypoxic injury. Methods In preterm (0.6 gestation) fetal sheep, dobutamine (Dob, 10 μg/kg/min) or saline (Sal) was infused intravenously for 74 h. Two hours after the beginning of the infusion, umbilical cord occlusion (UCO) was performed to produce fetal asphyxia (Sal+UCO:n = 9, Dob+UCO:n = 7), or sham occlusion (Sal+sham:n = 7, Dob+sham:n = 6) was performed. Brains were collected 72 h later for neuropathology. Results Dobutamine did not induce cerebral changes in the sham UCO group. UCO increased apoptosis and microglia density in white matter, hippocampus, and caudate nucleus, and astrocyte density in the caudate nucleus. Dobutamine commenced before UCO reduced microglia infiltration in the white matter, and microglial and astrocyte density in the caudate. Conclusion In preterm hypoxia-induced brain injury, dobutamine decreases neuroinflammation in the white matter and caudate, and reduces astrogliosis in the caudate. Early administration of dobutamine in preterm infants for cardiovascular stabilization appears safe and may be neuroprotective against unforeseeable cerebral hypoxic injury.